Region-growing permutation alignment approach in frequency-domain convolutive blind source separation - Wang, Lin; Ding, Heping; Yin, Fuliang (Canadian Acoustics, 2009)
A new alignment method was proposed to solve the problem in frequency-domain blind source separation (BSS). The new alignment method was based on an inter-frequency dependence measure involving the powers of separated signals. Bin-wise permutation alignment was applied across all frequency bins using the correlation of separated signal powers and the full frequency band was partitioned into small regions. These small regions were based on the bin-wise permutation alignment result and region-wise permutation alignment was performed in a region-growing manner. It was demonstrated that the convolutive separation problem was converted to instantaneous separation in each frequency bin through short-time Fourier transform (STFT). It was also observed that the correlation of bin-wise signal power ratio tended to be high when the two components belonged to the same source.